(3GdJNWjW GdSjGMj (B:s (3aj SHjd JNWjW ecGfj TGed heJcGed (B/s - (3Zfje, YKeGf eMeOs; (3HfjJG, fHjd SYOs ((3YeGf(B: s (3OGQ UaGA ddfTQ(B, s, 1999)
(3GdSjGMI hGdfTGWGJ GdSjGMjI,GdJNWjW GdSjGMj hGdJfejI GdSjGMjI,GdJNWjW GdSjGMj aj GdeSJhjjf GdhWfj hGdEbdjej,GdJNWjW GdSjGMj aj GdeSJhi GdeMdj,GdJNWjW GdSjGMj hGdBKGQ GdHjFjI hGdEbJUGOjI hGdELJeGYjI,GdYfGUQ GdJNWjWjI hGdeDSSjI ddSjGMI hJfajP GdNWI GdSjGMjI,GdJNWjW GdSjGMj hGdJLQHI GdCQOfjIs
(3HjHdjhZQGajG (B:(3U(B.231s
Keywords: (3GdSjGMIs; (3GdSjGMI (B- (3GdGQOfs; (3GdSjGMI(B: (3GdJNWjWs